Determining the Deposition Rate of Semiconducting Intrinsic Layer Prepared by Nanospray Method - Aulia Anisa Firdaus; Endhah Purwandari; Retno Asih; Ahmad Sholih; Darminto Darminto (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2023)
Amorphous carbon (a-C) film provides potential ability as an i-type layer in semiconductor material for photovoltaic purposes due to its tunable properties. Here, we investigate how to get the deposition rate estimation of the thickness and homogenous surface of a-C film as an i-type in solar cell applications. The a-C was prepared from palmyra liquid sugar using nebulizer as a nanospray method. The thick palmyra liquid sugar was carbonized at 250◦C for 2.5 hours then continued at 300◦C for 2 hours to obtain high-carbon charcoal. The thickness was examined using a SEM cross section, and the amorphous phase was measured using XRD. The amorphous characteristic of a-C is confirmed by broad peaks in XRD patterns. The thickness of a-C films was found to be thinner than in a previous study that used a similar materials and methods but different equipment in the deposition process. The average thickness of a-C films is in the range of 200 to 450 nm, followed by an increase in the deposition time of 5 to 25 s. By these value, the deposition rate estimation was obtained using extrapolation linier method from the SEM result around 11.62 nm/s. This result can be used as a reference to make various thicknesses for the i-layer in order to find the maximum thickness that gives high efficiency to amorphous carbon film.